2016
DOI: 10.1002/jcu.22400
|View full text |Cite
|
Sign up to set email alerts
|

Fetal stomach and gallbladder in contact with the bladder wall is a common ultrasound sign of stomach‐down left congenital diaphragmatic hernia

Abstract: Recognition of the fetal stomach and/or gallbladder in contact with the bladder wall can help in the detection of stomach-down left CDH. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45:8-13, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Morgan et al . hypothesized that this remarkable finding was due to the absence of bowel in the abdomen 3 . In agreement with this hypothesis, the only other condition in which we have observed the stomach to be in contact with the bladder is gastroschisis (Figure 2; unpubl.…”
Section: Figuresupporting
confidence: 84%
See 3 more Smart Citations
“…Morgan et al . hypothesized that this remarkable finding was due to the absence of bowel in the abdomen 3 . In agreement with this hypothesis, the only other condition in which we have observed the stomach to be in contact with the bladder is gastroschisis (Figure 2; unpubl.…”
Section: Figuresupporting
confidence: 84%
“…Moreover, based on our series, Morgan et al reviewed retrospectively a large cohort of pregnancies with CDH and similarly found that the stomach was in contact with the bladder in two-thirds (15/22; 68%) of the subset of fetuses with stomach-down left CDH 3 that the gallbladder was in contact with the bladder in 75% of cases. Morgan et al hypothesized that this remarkable finding was due to the absence of bowel in the abdomen 3 . In agreement with this hypothesis, the only other condition in which we have observed the stomach to be in contact with the bladder is gastroschisis (Figure 2; unpubl.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…We agree that abnormal orientation of the stomach resulting in it being in contact with the urinary bladder can be seen in 'stomach-down' left congenital diaphragmatic hernia (CDH). In our cohort, we identified this finding on ultrasound and, when available, magnetic resonance imaging (MRI) in 12/28 (42.9%) fetuses with stomach-down left CDH, which is slightly lower than the previously reported incidence 2,3 . Interestingly, we identified that gestational age was greater in fetuses with the stomach in contact with the bladder compared to those without (mean, 34 + 5 weeks vs 28 + 6 weeks; P < 0.01), suggesting that increased stomach distension and shift of intra-abdominal content over the course of gestation may be a contributing factor.…”
Section: Replymentioning
confidence: 61%